2016
DOI: 10.1021/acs.jafc.5b05181
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into the Different Resistance Mechanism of Imidacloprid versus Dinotefuran in Bemisia tabaci

Abstract: Insecticide resistance is a critical problem for pest control and management. For Bemisia tabaci, striking high metabolic resistance (generally conferred by CYP6CM1) was observed for imidacloprid (IMI) and most other neonicotinoid members. However, dinotefuran (DIN) displayed very low resistance factors, which indicated distinct metabolic properties. Here, molecular modeling methods were applied to explore the different resistance features of IMI versus DIN within the Q type of CYP6CM1. It was found that Arg22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…2B), indicating that M. persicae with imidacloprid resistance obtained by the overexpression of CYP6CY3 will not show strong resistance to dinotefuran. As is the case of B. tabaci CYP6CM1, 12) it is possible that the binding of dinotefuran to CYP6CY3 is weak. Thus, the lack of metabolism of dinotefuran explains why the FCR strain has the same level of resistance against dinotefuran and sulfoxaflor.…”
Section: Resultsmentioning
confidence: 99%
“…2B), indicating that M. persicae with imidacloprid resistance obtained by the overexpression of CYP6CY3 will not show strong resistance to dinotefuran. As is the case of B. tabaci CYP6CM1, 12) it is possible that the binding of dinotefuran to CYP6CY3 is weak. Thus, the lack of metabolism of dinotefuran explains why the FCR strain has the same level of resistance against dinotefuran and sulfoxaflor.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 In B. tabaci, CYP6CM1 was shown to be highly associated with resistance to pymetrozine and imidacloprid, 19,20 and CYP6CM1vQ conferred distinct levels of resistance to dinotefuran and imidacloprid. 21 Recently, CYP4CS3, CYP4C64, CYP6CX2, CYP6CX4, CYP6CX5, CYP6DW2, and CYP6DW3 were linked to neonicotinoid insecticide resistance. 22,23 Similarly, GSTs also have an important role in the detoxification of several classes of insecticides such as organophosphate, pyrethroid, and neonicotinoid insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Flupyradifurone (Sivanto 200 SL) first became commercially available for use in Florida vegetables in 2015, shortly after the last populations in this study were collected from the field. Flupyradifurone possesses the same mode of action as the neonicotinoid insecticides, but like dinotefuran, is not detoxified by the microsomal monooxygenases, including the P450 gene CYP6CM1, that have been implicated in the development of resistance to imidacloprid and other neonicotinoid insecticides by B. tabaci [24,31,32]. Nauen et al [31] demonstrated that flupyradifurone lacks metabolic cross-resistance to imidacloprid.…”
Section: Discussionmentioning
confidence: 99%